Statistical method for the fatigue life estimation of coke drums. (February 2015) - Yan, Zhi; Zhang, Yanxiang; Chen, Jie; Xia, Zihui
Highlights: A statistical fatigue life estimation method for coke drum is proposed. Thermal–mechanical fatigue tests are performed on coke drum materials. Global and local stress/strain analysis models are established for coke drum. Statistical temperature distribution model on coke drum shell is developed. The predicted results of the new method are in consistent with industrial survey data. Abstract: Coke drums are vertical pressure vessels used in the delayed coking process in petroleum refineries. They are operated under severe thermal–mechanical conditions by cyclic heating and quenching processes, which make them susceptible to damage. To accurately predict the safety lives of coke drums, a statistical fatigue life evaluation method is proposed in this study. To develop this method, thermal–mechanical cyclic fatigue tests of coke drum materials were firstly conducted to obtain strain-life curves, then simplified thermal-elasto-plastic analytical models were developed to calculate maximum equivalent strain amplitudes for global cycling and local hot and cold spot events. Statistical analysis of temperature data on a coke drum shell was also performed to get the probability distributions of the hot and cold spot events. The final statistical fatigue life evaluation model is based on Palmgren-Miner's damage accumulation rule. The fatigue life of a selected coke drum is hereafter estimated according to the maximum equivalent strain amplitudes in both cladding and base plate. The predicted fatigue life of the coke drum is about 5000 operation cycles, which is within the range of operation cycles to the first-through-thickness crack in coke drums, reported by American Petroleum Institute (API) survey. The evaluation methodology developed in this study can be employed to predict the safety lives of coke drums and is expected to be helpful for the design and maintenance of the equipment.